Quantifying the ability of the CF2H group as a hydrogen bond donor - Matthew E. Paolella; Daniel S. Honeycutt; Bradley M. Lipka; Jacob M. Goldberg; Fang Wang (Beilstein Journal of Organic Chemistry)
The CF2H group can act as a hydrogen bond donor, serving as a potential surrogate for OH or SH groups but with a weaker hydrogen bond donation ability. Here, we describe a series of CF2H group-containing moieties that facilitate hydrogen bond interactions. We survey hydrogen bond donation ability using several established methods, including 1H NMR-based hydrogen bond acidity determination, UV–vis spectroscopy titration with Reichardt's dye, and 1H NMR titration using tri-n-butylphosphine oxide as a hydrogen bond acceptor. Our experiments reveal that the direct attachment of the CF2H group to cationic aromatic systems significantly enhances its hydrogen bond donation ability, a result consistent with theoretical calculations. We anticipate that this chemistry will be valuable for designing functional molecules for chemical biology and medicinal chemistry applications.